Induced pluripotent stem cell line (INSAi002-A) from a Fabry Disease patient hemizygote for the rare p.W287X mutation - Duarte, Ana Joana (2020)
Fabry Disease (FD) is a multisystemic X-linked disorder that belongs to the group of lysosomal storage disorders (LSDs). Causal mutations on alpha-galactosidase A (α-Gal A) commonly lead to abnormal protein and consequently to FD. Since it is an X-linked disease, males are primarily affected. This work describes the generation of induced Pluripotent Stem Cells (iPSCs) from skin fibroblasts from a FD patient, using non-integrative episomal vectors. Differentiation of iPSCs can be applied to generate a variety of cell types with high degree of genetic complexity that would otherwise be difficult to obtain.